Macroeconomic Equilibriums, Crises and Fiscal Policy - Fredrik N. G. Andersson (Lund University, School of Economics and Management, Department of Economics, 2020)
Macroeconomic crises are common as well as economically, socially and politically costly. Fiscal policy plays an important role in alleviating the costs of the crisis. However, recent experiences suggest that the public finances often are unprepared for a crisis. Deficits and debt levels prior to the crisis are commonly too high, limiting the governmentâ exteuro™s ability to respond to the crisis. In this paper, we argue that theoretical macroeconomic models focus on stable equilibriums, may partially explain why governments underestimate the risk of economic crises and carry too much debt prior to such events. In the standard equilibrium models, crises are one-off events caused by external factors. These macro-models thus neither predict nor expect a future crisis, which creates a false impression of long-run economic stability. Using forecast data, we demonstrate how the equilibrium perspective dominates macroeconomic thinking and how it contributes to too-high debt ratios prior to a crisis. We end the paper by discussing how to design fiscal policy rules based on a crisis rather than an equilibrium approach.
Keywords: E17; E37; E62; E63; 330; crisis; equilibrium; macroeconomic models; fiscal policy; national debt; fiscal frameworks